Unusual PSMA uptake in seronegative paraneoplastic brainstem encephalitis: A case report (Indian Journal of Case Reports, 2024)
Paraneoplastic encephalitis, especially seronegative, is a heterogeneous group of disorders with varied symptoms at presentation. We present the case of a 63-year-old male who presented with motor weakness and altered sensorium. Magnetic resonance imaging of the brain showed altered signal intensity in the midbrain, pons, anterior part of the medulla, and bilateral middle cerebellar peduncle. T2 hyperintensity was also seen in the bilateral basal ganglia and internal capsule region. 18 fluoro-deoxyglucose positron emission tomography/computed tomography (18 FDG PET/CT) showed increased FDG uptake in the brain stem, left thalamus, and periventricular location. 68Ga-prostate-specific membrane antigen (PSMA) PET/CT done in view of elevated serum Prostate-specific antigen levels show a focal PSMA-avid lesion in the prostate gland and increased PSMA uptake in the brain stem, which is an atypical site of PSMA uptake. Our study highlights the importance of paraneoplastic syndromes with varied clinical presentation and low specificity to antibodies. These spectra of diseases are fatal but treatable and therefore should be evaluated diligently to reduce morbidity